CORRECTION OF NEGATIVE MENTAL STATES OF CADETS WITH THE HELP OF VIRTUAL REALITY TECHNOLOGIES - Safin, Oleksandr; Mas, Natalia (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2024)
B a c k g r o u n d . Virtual reality technologies can be used to optimize many mental states and develop mental resources. Virtual reality technologies work with the imaginative sphere, recreating images around the subject that are close to those of real people and objects. Methods of psychological correction that work with the imagery are traditionally used to help people relax and relieve stress.M e t h o d s . The DAS questionnaire (Differential assessment of states of reduced performance "fatigue-monotony-satiety-stress") (A. Leonova, S. Velichkovska), the Scale for assessing the level of reactive and personal anxiety (C. Spielberg, Y. Khanin), the Assessment of mental activation, interest, emotional tone, tension and comfort (L. Kurgansky and L. Kumiansky), the Questionnaire for assessing acute physical fatigue (A. Leonova), the Assessment of acute mental fatigue (A. Leonova, S. Velichkovska). Kurgansky and L. Kumiansky), Questionnaire for Assessment of Acute Physical Fatigue (A. Leonova), Questionnaire for Assessment of Acute Mental Fatigue (A. Leonova, N. Savicheva), Akiyoshi Kitaoka Optical Illusion Test (a technique aimed at measuring situational fatigue syndrome).R e s u l t s . The main methods of correction of mental states with the help of virtual technologies are highlighted. The use of virtual reality technologies in the educational sphere is analyzed. It is shown that during the education day, cadets accumulate negative emotional states in the process of classes: fatigue, tension, situational fatigue, monotony.C o n c l u s i o n s . The use of virtual reality technology to immerse a cadet in a virtual space allows you to restore mental resources and delay the development of negative states. For the development of mental resources, the correct selection of virtual realities is of great importance. Thus, watching relaxation-type virtual reality stories leads to a decrease in the level of fatigue, and dynamically stimulating type with the effect of presence leads to a decrease in the level of situational fatigue.
Keywords: negative mental states, cadet, correction of mental states, virtual reality technologies, mental resources